(untitled) (MATEMATIKA, 2006)
Assignments of lecturers to courses is one of the problems in education management (or planning) especially in higher institutions such as universities or colleges. This paper investigates the feasibility of determining an optimal assignment of lecturers to courses under various conditions using an operations research method. Beginning with the classic general almost ``free entry" or ``unrestricted" pure transportation model of linear programming, the problem is extended to include possibilities such as course-sharing and time-tabling clashing. This leads to the formulation of a revised zero-one integer programming model. The results of some empirical tests are also reported. Keywords: Assignment; zero-one integer programming